Late Fauzan represented by his brother - Nor Salwana, Mohammad Idris (UMPSA, 2023)
GAMBANG, 21 October 2023 - A brother was overcome with grief as he represented his parents to receive a Posthumous Award for his deceased brother at Universiti Malaysia Pahang Al-Sultan Abdullah’s (UMPSA) 18th Convocation Ceremony at the UMPSA Sports Complex Hall.